Beyond online and offline activism: #SaveSheikhJarrah and contemporary resistance in Palestine - Daniele, G.; Kelsch, S. (Journal of International and Intercultural Communication, 2025)
This article focuses on the interconnections between online and offline activism in Palestine, with a detailed analysis of the case of Sheikh Jarrah (east Jerusalem). We examine current strategies of Palestinian digital resistance that have highlighted the relevance of interlinking struggles both at the grassroots level and on the internet. Within the settler colonial framework, the hashtag #SaveSheikhJarrah stands as one of the most emblematic contemporary struggles against the Israeli military occupation, particularly against the ongoing evictions taking place in areas such as Sheikh Jarrah in east Jerusalem and the West Bank. In recent years, this hashtag has drawn unprecedented global attention to the Palestinian cause. This article is based on extensive digital ethnography and semi-structured interviews with young Palestinian activists conducted from 2021 to 2023. Through an exploration of activists’ narratives surrounding the #SaveSheikhJarrah movement, we critically examine the interplay of diverse forms of resistance in the age of social media. Our lens of analysis links grassroots and online struggles, offering a fresh perspective on digital activism in the current discourse on culture and communication within Palestinian studies.